Integrated weed management for doubling farmers’ income - Yaduraju, N. T.; Mishra, J. S. (Indian Farming, 2018)
There is enormous scope for enhancing the farmers’ income by lowering the cost on weed control and by achieving higher productivity. Timely weeding and raising a healthy crop are critical in our fight against the onslaught of weeds. A number of preventive and cultural methods and minor changes in agronomic practices have a very significant bearing on weed competition. With judicious use and clever integration with other methods of weed management, herbicides will enable farmers to achieve better weed control at reduced cost and very often with enhanced productivity of crops. However, IWM being a knowledge intensive activity requires the support and patronage of weed scientists and extension personnel. Farmers need to be sensitized in popularizing the benefits of the technology.